Analisis rantai nilai dalam aspek lingkungan dan ekonomi menggunakan VCOR pada petani kopi di Malang - Imam Santoso; Miftahus Sa'adah; Izzum Wafi'uddin; Naila Maulidina Lu'ayya; Dodyk Pranowo; Retno Astuti (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
The coffee agroindustry in Indonesia, particularly in Malang Raya, has undergone expansion through the increased development of coffee processing industries, including waste and emissions. Various factors, including farming practices, land use, waste management, and the utilization of by-products influence the emission levels in the supply chain. A value chain analysis in supply chain management is essential to support sustainable coffee agroindustry. The complexity of the coffee value chain involves multiple stakeholders, including input providers, producers, traders, cooperatives, and exporters, emphasizing the intricate nature of the coffee chain and the need for coordinated efforts to ensure quality and sustainability. This research aims to identify emission sources in the supply chain and determine the economic impact of coffee production at the farmer level. The value chain operations reference is the method used for measuring the value chain. The calculation results indicate that the carbon emission footprint in the supply chain activities at the farmer level amounts to 22,734 kg CO2 with a unit cost of 0.75 €/kg. These values suggest that activities in the coffee value chain at the farmer level are still not environmentally friendly (intolerable region). Suggested approaches for enhancing the value chain for coffee farmers in Karangploso encompass the installation of a smart GPS system in vehicles for route optimization and fuel efficiency, and using organic fertilizers instead of chemical fertilizers to prevent water pollution, along with the adoption of an organic farming system to enhance the economic value of the harvest. The findings of this study are expected to be a reference for research on the value chain in coffee supply chain activities, and contribute to the enrichment of information related to the VCOR model